1984
DOI: 10.1099/0022-1317-65-10-1839
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide Specificity of the Early Antibody Response Following Primary and Recurrent Genital Herpes Simplex Virus Type 2 Infections

Abstract: SUMMARYRelative IgG titres to specific viral proteins in acute and convalescent sera from patients with primary and recurrent genital herpes simplex virus type 2 (HSV-2) infections were determined using an immunoblot assay. Patients with recurrent genital infections generally had high titres of antibody reactive with two of the three major viral glycoproteins (gD and gG) as well as with several viral capsid proteins in both acute and convalescent sera. In contrast, patients experiencing primary genital HSV-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…40K and 43K, while the group of antigens from 40K to 49K included two or three other proteins which also appeared to be major targets of the convalescent antibody response. Previous reports based on immune precipitation of human (Ashley & Corey, 1984;Zweerink & Corey, 1982) or guinea-pig sera (Ashley & Kern, 1984) have not described these as major antigens, while other studies employing immunoblotting techniques (Eberle et al, 1984) have noted findings similar to ours (Bernstein et al, 1984a). This suggests that these polypeptides are either poorly labelled or solubilized and are thus not readily detected by immune precipitation.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…40K and 43K, while the group of antigens from 40K to 49K included two or three other proteins which also appeared to be major targets of the convalescent antibody response. Previous reports based on immune precipitation of human (Ashley & Corey, 1984;Zweerink & Corey, 1982) or guinea-pig sera (Ashley & Kern, 1984) have not described these as major antigens, while other studies employing immunoblotting techniques (Eberle et al, 1984) have noted findings similar to ours (Bernstein et al, 1984a). This suggests that these polypeptides are either poorly labelled or solubilized and are thus not readily detected by immune precipitation.…”
Section: Discussionmentioning
confidence: 62%
“…Investigators employing immune precipitation of radiolabelled HSV polypeptides and SDS-polyacrylamide gel electrophoresis have observed a major response to the glycoproteins of HSV (Zweerink & Corey, 1982;Gilman et al, 1981 ;Ashley & Corey, 1984), an expected finding since these surface glycoproteins appear to represent the immunologically most important viral antigens. More recently, we (Bernstein et al, 1984a) and others (Eberle et al, 1984) have reported on the immune response to lower molecular weight non-glycosylated proteins [ranging from mol. wt.…”
Section: Introductionmentioning
confidence: 99%
“…Most immune sera from HSV-infected individuals react with 12 to 20 viral polypeptides in immunoblots. The envelope glycoproteins gB, gD, gC, gE, and gG, the major capsid protein VP5, and the nucleocapsid complex p40 have been identified as primary targets of IgG antibody responses in patients with HSV-1 and/or HSV-2 infections (2,5,13,14,38). The B virus's homology to HSV-1 (79.9% amino acid identity for gB, 57% identity for gD, 49.9% identity for gC, 46% identity for gE, and 29.2% identity for gG [42]) suggests that the specificity of B virus-induced antibody responses is similar to that of responses induced by HSV types 1 and 2.…”
mentioning
confidence: 99%
“…These proteins are probably related to the p40 protein purified from HSV nucleocapsids by Heilman et al (198 1) because monoclonal antisera to p40 (Zweig et al, 1980) bind to a series of proteins ranging in mol. wt (lo3) from 34 to 49 (Eberle et al, 1984(Eberle et al, , 1985. It is also possible that antibody to viral thymidine kinase (mol.…”
Section: Discussionmentioning
confidence: 99%